1980
DOI: 10.1002/mrc.1270130616
|View full text |Cite
|
Sign up to set email alerts
|

Selection of shift reagents for 17O NMR. Application to line assignments

Abstract: Chemical shifts and line broadenings induced by a series of lanthanide dipivaloylmethanates Ln(dmp), on the 0 NMR signal of methanol have been measured. The best high-field shift reagents are those containing the cations Tb+, and D Y +~; very large shifts have been observed for even quite low concentrations of reagent.The shift reagents are able to discriminate between different oxygen functions and can, in principle, be used for line assignments. 17Chelates of lanthanide ions have been commonly used in 'H NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This fact can be related with the high stability of cyclopropenones, [37] despite their high ring strain [38] and in contrast to cyclopropanones and cyclopropenes, attributed to resonance stabilization by its polar formula which represents a pseudoaromatic system. Such a high shielding is only observed for the exocyclic oxygen atom of sydnone (d 232) [40] and related mesoionic compounds which are currently formulated with À O À in the place of O. Such a high shielding is only observed for the exocyclic oxygen atom of sydnone (d 232) [40] and related mesoionic compounds which are currently formulated with À O À in the place of O.…”
Section: Resultsmentioning
confidence: 99%
“…This fact can be related with the high stability of cyclopropenones, [37] despite their high ring strain [38] and in contrast to cyclopropanones and cyclopropenes, attributed to resonance stabilization by its polar formula which represents a pseudoaromatic system. Such a high shielding is only observed for the exocyclic oxygen atom of sydnone (d 232) [40] and related mesoionic compounds which are currently formulated with À O À in the place of O. Such a high shielding is only observed for the exocyclic oxygen atom of sydnone (d 232) [40] and related mesoionic compounds which are currently formulated with À O À in the place of O.…”
Section: Resultsmentioning
confidence: 99%
“…Dy(dpm) 3 and Tb(dpm) 3 (dpm: 2,2,6,6-tetramethylheptane-3,5-dionate) and Eu(fod) 3 (fod: 6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5-octanedionate) have been shown to be the most effective shift reagents in 17 O NMR [167][168][169][170]; the mechanism is essentially due to the contact and pseudo-contact shift (see Section 8.5). The shift effect for carbonyl oxygen, extrapolated to [Dy(dpm) 3 ]:[substrate] = 1, is several thousand ppm to low frequency.…”
Section: Use Of Lanthanide Shift Reagentsmentioning
confidence: 99%
“…Oxygen-17 shieldings are significantly influenced by lanthanide shift reagents due to complexation which can be utilized for resolution enhancement and assignment purposes [167]. Dy(dpm) 3 and Tb(dpm) 3 (dpm: 2,2,6,6-tetramethylheptane-3,5-dionate) and Eu(fod) 3 (fod: 6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5-octanedionate) have been shown to be the most effective shift reagents in 17 O NMR [167][168][169][170]; the mechanism is essentially due to the contact and pseudo-contact shift (see Section 8.5).…”
Section: Use Of Lanthanide Shift Reagentsmentioning
confidence: 99%
“…However, more recent experiments with effects on 1 of lanthanide shift reagents revealed that it is the resonance of the more shielded oxygen nucleus which is essentially affected, and the latter was tentatively assigned to the exocyclic oxygen. 17 This has finally been proven by the 17 O spectra of specifically labelled 1 and arguments based on the unusually high magnetic shieldings of 17 O in cyclopropanones. 18 A comparison of the computed and experimental 17 O shieldings (Table 4 and Fig.…”
Section: Resultsmentioning
confidence: 88%